Service touristic profile: english and spanish for you - Ayala Esquivel, Yanci Amelia
Many people think that tourism is only to travel to another country, or has money to do it, however tourism is to go anywhere and exchange your culture and beliefs with others. Whether this place is near or far from home. This report presents the way to create a touristic service through four chapters. The name of it is English and Spanish for you (ES4U). This with the objective to create employment to the people who need it in the area and to provide the access to this tool to Chiltiupan, La Libertad. The tourism industry has been growing during the last years in El Salvador, but it is still important to contribute, so that, this service can provide English as a tool for those who want to work in restaurants. Moreover, language tourism is to spend one or more than one year in a place that is not your natural environment to learn and practice a language different from yourself. This proves that people are interested in learning new languages, whether English or Spanish. This means this academy can have a big impact Chiltiupan and the surrounded municipalities. To finish with, all the characteristics proved this is an entrepreneurship by opportunity. Key words: Field trips ; academy ; touristic language ; tourism ; English